2013
DOI: 10.2134/agronj2013.0115
|View full text |Cite
|
Sign up to set email alerts
|

Spikelet Sterility is Associated with a Lack of Assimilate in High‐Spikelet‐Number Rice

Abstract: New rice (Oryza sativa L.) genotypes bearing a high spikelet number (HS) occasionally cannot show their high yield potentials due to the lower grain‐filling rate. Our objectives were to evaluate the effect of spikelet sterility on grain filling in HS cultivars and to determine whether the assimilation factor around anthesis is related to spikelet sterility. Two japonica × indica and one japonica × javanica HS cultivars were grown and compared with single‐standard indica and japonica rice cultivars. Lower spike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 32 publications
(50 reference statements)
1
13
0
Order By: Relevance
“…Currently, increasing evidence has demonstrated that non-structural carbohydrates, the main source of the dry matter stored in vegetative organs, not only function as an assimilate supply for grain filling but also play a critical role in enhancing sink activity during rice grain filling 31 , 32 . This fully embodies the importance of dry matter accumulated in vegetative organs before heading for determining sink capacity and final grain yield 33 , 34 . In the present study, we further found that in regard to mechanical-transplanted rice that experienced delayed transplantation, enhancing the amount of pre-anthesis dry matter remobilization and the contribution to grain yield was an effective channel to increase sink capacity per tiller regardless of cultivation density.…”
Section: Discussionmentioning
confidence: 94%
“…Currently, increasing evidence has demonstrated that non-structural carbohydrates, the main source of the dry matter stored in vegetative organs, not only function as an assimilate supply for grain filling but also play a critical role in enhancing sink activity during rice grain filling 31 , 32 . This fully embodies the importance of dry matter accumulated in vegetative organs before heading for determining sink capacity and final grain yield 33 , 34 . In the present study, we further found that in regard to mechanical-transplanted rice that experienced delayed transplantation, enhancing the amount of pre-anthesis dry matter remobilization and the contribution to grain yield was an effective channel to increase sink capacity per tiller regardless of cultivation density.…”
Section: Discussionmentioning
confidence: 94%
“…Ito et al 28 and Chen et al 29 reported that the high temperature at the grain filling period will decrease the quality of the rice. Moreover, a high seed filling rate and short seed filling duration cause stress, impacting seed growth and development 8,9 . Therefore, it can be speculated that a lower seed filling rate and longer seed filling duration observed at low temperature during seed filling period could positively increase the seed vigor of hybrid rice during seed production.…”
Section: Discussionmentioning
confidence: 99%
“… Kobata et al (2013) and Yoshinaga et al (2013) suggested that in these high-yield cultivars, spikelet fertility contributes to poor grain filling. In this study, we found that SS removal significantly improved the IS seed setting rate in strains W1844 and WJ165.…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible reasons for this occurrence. First, inadequate assimilate supply around flowering results in spikelet sterility through a fault in the pollination process ( Kobata et al, 2013 ); therefore, after SS removal, the number of fertilized grains increases with increases in the IS assimilate supply. Secondly, blighted IS grains transformed into plump grains because they obtained an adequate supply of assimilates.…”
Section: Discussionmentioning
confidence: 99%